In Vivo MR Imaging of the Flow of the Brain Interstitial Fluid - Liu, Bin; Zhang, Cunjing; Li, Yuliang (Neuroscience and Biomedical Engineering (Discontinued), 2016)
Objectives: To image the flow of the brain interstitial fluid (ISF) in the deep nuclei. Materials and Methods: We developed a tracer-based MRI method. Gadolinium-diethylene triamine pentaacetic acid (Gd-DTPA) was used as a probe to trace the flow of the brain ISF, and was introduced into the brain ISS with the aid of sterotecix at four different sites: 1) caudate nucleus (Cn.); 2) thalamus (T.); 3) cortex (Cor.); and 4) substantia nigra (Sn.). The probe shortened the spin-lattice relaxation time of hydrogen nuclei in water molecules of brain ISF and presented as high signal on MRI. The local enhancement in the rat brain on MRI decreased over time due to the water diffusion or clearance process within the brain interstitial space (ISS). The process was dynamically recorded on a series of MR scans. As the increment in signal intensity (ΔSI) could be converted to local Gd-DTPA concentration, the flow parameters of the brain ISF can be quantitatively measured and imaged. Results: Among the four areas, the Cn. has the most extensive distribution from the injection points to the ipsilateral frontal and temporal cortices. The traced brain ISF in Cor. extended horizontally to its adjacent cortex, and no centripetal flow toward deep brain was demonstrated. By comparison, the enhancement localized within their anatomical divisions in thalamus and substantia nigra instead of diffusion outside. The local diffusion parameter β of thalamus and cortex were greater than that of the other two areas. (F = 19.60, P <0.05). Conclusion: The different distribution territories and clearance rates of the probe in different brain areas indicated that the brain ISS is a physiologically partitioned system.
Keywords: substantia nigra